Experiências e territórios da loucura: narrativas de portadores de sofrimento mental assistidos em um serviço aberto na cidade de Belo Horizonte - Amanda Elias Arruda (2016)
Through fieldwork conducted at the Mental Health Service in the city of Belo Horizonte, we identified the relevance of analyzing the relationship between experience mentally illness patients and the City of Belo Horizonte/ MG. The primary objectives of this research were twofold 1) understand the creation, evolution and current status of this community service and 2) analyze the life trajectory of patients from a life experience and interpersonal relationship standpoint and the relationship with the city. The research is aligned with the analysis of the dynamics of everyday relationships in the social world. The concept of experience adopted by the phenomenological sociology is the starting point for understanding the experiences of mental illness. From a biographical standpoint, we seek to write an ethnographic narrative.Thus, we performed our fieldwork through the collection of data and observations from the East Regional Mental Health Reference Center (CERSAM East); the development of questioners, conduction of interviews, analysis of historical data from CERSAM and biographies of three people assisted this in undertaking. The records were obtained through sound recordings, notes, diaries, records and documents retrieved from the CERSAM archives. We discovered that the creation of this public service was the result of political struggles. The creation of this public service was based on the tension between total institution and openservice and the destruction of myths associating mental sickness and violence. The biographical narratives revealed diverse experiences associated with mental illness as well as different meanings attributed to this condition. However, interestingly, these stories have a common pattern, often associated with dispossession through the weakening of family ties and exclusion from having a full and productive life, which ultimately leads to an existence of marginality. Public space, predominately streets, are the primary locations where this life trajectories takes place. The repossession phenomenon is present in every path. New codes and territories coexist including art, political activism; the wandering, begging; and drug use and informal work. We verify the permanence of the stigma of madness; however, individiuals with a history of mental illness resists this stigma as they come out of invisibility and in doing so manipulate social codes and create new territories and encodings.